Male and Female Archetypes in Doctor Who. - Layton, David (Consciousness, Literature & the Arts, 2010)
The article explores the depiction of male and female archetypes in Great Britain's primary science fiction television series "Doctor Who." It mentions that individual stories in the said program follow ancient patterns of mythic storytelling. It also believes that "Doctor Who" has become the main theme to English culture because of the iconic status of its oldest villains which are the cyborg-warrior collective race known as Daleks.